Мемуары и дневники петербургских купцов конца XVIII - начала XX в. в новейших отечественных исследованиях по истории предпринимательства и купечества (Библиосфера)
The article is devoted to the problems of history of St-Petersburg merchants' memoirs and diaries (the late XVIII - early XX century) studying in modern Russian historiography The basic research on the history of entrepreneurship and merchants of Russia, released after 1991, and reflection in them the memoirs of Petersburg merchants as a source are considered. The way of using certain memoirs and diaries is analyzed, general conclusions on trends in their studying by modern scholars are made.